Assessment Of The Effect Of Socio-Economic Infrasturcture On Rural Economy In Kaduna State, Nigeria - Saheed, Zakaree S.; Obianuju, Chima K. (European Scientific Journal, ESJ, 2021)
The paper examines the effect of socio-economic infrastructure of the rural areas on the rural economy in Kaduna State. The study adopts a correlation analysis, a Multicollinearity and Cronbach Alpha Reliability tests as well as regression analysis on primary data. Findings from the study reveal that there is a positive relationship between socioeconomic infrastructure and rural economy, while the multicollinearity test shows absence of high correlation among the independent variables and the Cronbach Alpha confirms internal consistency of the variables. Furthermore, the regression analysis indicates that socio-economic infrastructure, particularly road, electricity supply, market and telecommunication infrastructure all have positive and statistically significant effects on the rural economy. The paper therefore, recommends that governments should increase efforts towards developing the infrastructure in the rural areas in order to facilitate the growth of the economy in the rural sectors.